How Did COVID-19 Change Opinions and Behaviors in the Netherlands? - Antonides, Gerrit; Goedegebure, Robert; van Leeuwen, Eveline (Frontiers in Sustainable Cities, 2022)
The early stages of the COVID-19 pandemic may have led to a number of behavioral adaptations among Dutch citizens, possibly due to restrictions because of lockdowns, changed orientations toward work, and changes in consumer sentiment. These factors theoretically predict a number of changes in behavior that may have affected people in diverse circumstances in different ways. Among the variables that we study are financial behaviors, health, happiness and emotions. We explore how these variables were affected among households with different sociodemographic conditions, including urbanization, income, gender and age. We use representative panel data from 2019 and 2020 including relevant information from about 2,800 Dutch citizens to study a number of changes primarily during the initial lockdown period in 2020 as compared with the normal situation in 2019. We use regression analysis to estimate the Difference-in-Difference effects of the lockdown in 2020 as compared with the state of affairs in 2019. We find several lockdown effects on transitory thoughts and feelings, i.e., price perceptions, household financial management, emotions, and social relations, of which some effects strongly differ between urban and rural areas. We did not find evidence for more long-lasting effects, for example, on savings, perceived health, and (un)healthy behaviors, although these might have occurred later during the pandemic.